Advanced nitrogen removal performance and microbial community structure of a lab-scale denitrifying filter with in-situ formation of biogenic manganese oxides. (1st April 2023) - Cheng, Qingfeng; Liu, Zongyang; Huang, Yang; Feng, Shanshan; Du, Erdeng; Peng, Mingguo; Zhang, Jie
Abstract: Advanced nitrogen removal faces the challenges of high operational cost resulted from the additional carbon source and secondary pollution caused by inaccurate carbon source dosage in municipal wastewater. To address these problems, a novel carbon source was developed, which was the oxidation products of refractory organic matters in the secondary effluent of municipal wastewater treatment plant (MWWTP) by in-situ generated biogenic manganese oxides (BMOs) in the denitrifying filter. In the steady phase, the effluent chemical oxygen demand (CODcr ), NO3 − -N and total nitrogen (TN) in the denitrifying filter 2 # with BMOs was 11.27, 9.03 and 10.36 mg/L, and the corresponding removal efficiency was 54.79%, 51.85% and 48.03%, respectively, which was significantly higher than those in the control denitrifying filter 1 # that the removal efficiency of CODcr, NO3 − -N and TN was only 32.30%, 28.58% and 29.36%, respectively. Kinds of denitrifying bacteria ( Candidatus Competibacter, Defluviicoccus, Dechloromonas, Candidatus Competibacter, Dechloromonas, Pseudomonas, Thauera, Acinetobacter, Denitratisoma, Anaerolineae and Denitratisoma ) and anammox bacteria ( Pirellula, Gemmata, Anammoximicrobium and Brocadia ) were identified in the denitrifying filters 1 # and 2 #, which explained why the actual CODcr consumption (1.55 and 1.44 mg) of reducing 1 mg NO3 − -N was much lower than the theoretical CODcr consumption. While manganese oxidizing bacteria (MnOB, Bacillus, Crenothrix and Pedomicrobium ) was only identified in the denitrifying filter 2 # . This novel technology presented the advantages of no additional carbon source, low operational cost and no secondary pollution. Therefore, the novel technology has superlative application value and broad application prospect. Graphical abstract: Image 1 Highlights: The existence of BMOs greatly improved the removal rate of CODcr, TN and NO3 − -N. The oxidation products of refractory organic matters were used as carbon source. The actual CODcr consumption for denitrification was distinctly decreased. Advanced nitrogen removal with low cost and no secondary pollution was achieved. Mn 2+ oxidation and denitrification occurred simultaneously in denitrifying filter 2 # .